PHOTOCATALYTIC DEGRADATION OF RHODAMIN-B USING METAL COMPLEXES AND HYDROGEN PEROXIDE - Savitri Lodha; Abhilasha Jain; Mukesh Paliwal; Pinki B. Punjabi (Indonesian Journal of Chemistry, 2008)
The photocatalytic degradation has been considered to be an efficient process for degradation of organic pollutants, which are present in the effluents released by industries. The photocatalytic bleaching was carried out on rhodamin-B (cationic dye) in the presence of iron (III) complex, hydrogen peroxide and was observed spectrophotometrically. The effect of various operating variables like pH, concentration of complex and dye, amount of H2O2 and light intensity etc. was also observed on the efficiency of the reaction. A tentative mechanism has also been proposed for this photocatalytic degradation of rhodamin-B.